Niels Kofoed: Myte og intellekt - Michelsen, William (Grundtvig-studier, 1970)
Niels Kofoed, Myte og intellekt. Munksgaardserien no. 24 Rev. by William Michelsen The primary purpose of this book is to place Grundtvig and Kierkegaard in modern European culture, and thereby offering a closer analysis of their connection with romanticism, seen in the light of Giambattista Vico’s view of history, according to which three epochs are cyclically repeated, viz. those of imagination, reason, and a “living union” of reason, imagination, and sensibility. Moreover, Kofoed considers the two Danish authors in the light of C. G. Jung’s psychoanalysis, in which respect he bases his work on Hjalmar Sundén, the religious psychologist (Religionen och rollerna3 Stockholm, 1959) and on an interpretation of “ Nyaars-Morgen” that comes close to Jørgen Elbek’s. – Even though the application of a cyclical view of history on Grundtvig and Kierkegaard, of all men, must be looked upon with skepticism, the book does contain valuable clues to an assessment of Grundtvig’s poetry.